2021
DOI: 10.3390/ijerph18189730
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Secondary Methylation Capacity Is Inversely Associated with Arsenic Exposure-Related Muscle Mass Reduction

Abstract: Skeletal muscle mass reduction has been implicated in insulin resistance (IR) that promotes cardiometabolic diseases. We have previously reported that arsenic exposure increases IR concomitantly with the reduction of skeletal muscle mass among individuals exposed to arsenic. The arsenic methylation capacity is linked to the susceptibility to some arsenic exposure-related diseases. However, it remains unknown whether the arsenic methylation capacity affects the arsenic-induced reduction of muscle mass and eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 90 publications
(162 reference statements)
0
9
0
Order By: Relevance
“…Epidemiological and animal studies have shown that arsenic exposure is associated with skeletal muscle mass loss and atrophy 8–12 . A previous in vivo study showed that exposure to 0.5 ppm As 2 O 3 for 4 weeks induced skeletal muscle atrophy in mice 37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological and animal studies have shown that arsenic exposure is associated with skeletal muscle mass loss and atrophy 8–12 . A previous in vivo study showed that exposure to 0.5 ppm As 2 O 3 for 4 weeks induced skeletal muscle atrophy in mice 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological and animal studies have shown that arsenic exposure is associated with skeletal muscle mass loss and atrophy. [8][9][10][11][12] A previous in vivo study showed that exposure to 0.5 ppm As 2 O 3 for 4 weeks induced skeletal muscle atrophy in mice. 37 The results of this study showed that exposure to 10 ppm arsenite for 3 months had no significant impact on skeletal muscle, while exposure to arsenite for 9 months caused significant loss of skeletal muscle mass and atrophy in rats.…”
Section: Arsenic Exposure and Skeletal Muscle Atrophymentioning
confidence: 99%
See 1 more Smart Citation
“…GFP fluorescence is dependent on correct protein folding, and arsenic exposure results in protein misfolding [ 56 , 57 ]; therefore, the reduced green fluorescent signal in gravid adults exposed to 25 µg/mL or more NaAsO 2 could be due to conserved arsenite-induced protein unfolding. However, arsenic exposure in humans is also associated with reduced muscle mass [ 58 ], suggesting that the reduced GFP could have been caused by changes in C. elegans muscle mass or myo-3 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…As affects the gluconeogenesis in muscle cells by inhibiting glucose transporters and suppressing glucose metabolism regulatory genes. Hence, the glycolytic pathway and mitochondrial energy production are altered [ 132 , 133 ]. In experimental studies of mice, it has been reported that As decreases the functional capacity of muscle and destroys muscle progenitor cells [ 134 ].…”
Section: Arsenic-induced Health Hazardsmentioning
confidence: 99%